Effect of prophylactic noninvasive oxygen therapy after planned extubation on extubation failure in high-risk patients: a retrospective propensity score-matched cohort study - Zheng, Xiaozhuo; Lu, Lixiong; Ma, Mengyi; Lei, Xiaofeng (Frontiers in Medicine, 2024)
Background Extubation failure (EF) is common in the intensive care unit (ICU) and is associated with poor prognosis, especially in high-risk patients. However, the efficacy of prophylactic noninvasive oxygen therapy (NIT), including noninvasive ventilation (NIV) and high-flow nasal cannula (HFNC), in reducing EF in high-risk patients remains controversial. Therefore, we aimed to evaluate the effect of post-extubation prophylactic NIT on EF in high-risk patients. Methods This was a retrospective observational study conducted in the ICU from March 2018 to December 2023. We included adult patients at high risk for reintubation who were mechanically ventilated for over 24 h and successfully passed the spontaneous breathing trial (SBT). Immediately after extubation, patients underwent NIT or conventional oxygenation therapy (COT). The primary outcome was the EF rate within 7 days after extubation. Results There were 440 patients in the NIT group and 274 in the COT group. After propensity-score matching, 227 subjects were enrolled in each group. NIT reduced the rate of EF (18.0% vs. 34.3%, p < 0.001) and reintubation (10.5% vs. 18.2% p = 0.003) compared with COT, which was confirmed in propensity-matched cohort (17.6% vs. 32.2%, p < 0.001; 11.5% vs. 19.8%, p = 0.014). Multivariate logistic regression analysis indicated that prophylactic NIT (p = 0.001) and higher ROX index (p = 0.022) were associated with reduced risk of EF. While higher fluid balance (p = 0.013), higher RSBI (p < 0.001), and the occurrence of delirium (p = 0.032) may be the risk factors for EF. Subgroup analysis showed that post-extubation NIT was more effective in elderly patients, and HFNC was non-inferior to NIV in reducing EF. While HFNC had a tendency to reduce the incidence of delirium. Conclusion Post-extubation prophylactic NIT is effective in reducing EF in high-risk patients, especially in the elderly patients. HFNC is an alternative treatment to NIV. Fluid balance, RSBI, ROX index, and delirium are associated with the occurrence of EF.